2022
DOI: 10.1039/d2sc02891c
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the end-to-end production of cyclic phosphate monomers with modular flow chemistry

Abstract: Biocompatibility, tunable degradability, broad functionalities of polyphosphoesters and their potential for biomedical applications stimulated a renewed interest from the Chemistry, Medicinal Chemistry and Polymer Sciences. Commercial applications of polyphosphoesters as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…Additionally, note that the efficient continuous flow method of the end-to-end preparation of cyclic phosphate monomers with a semi-continuous modular flow platform was developed very recently by Monbaliu and coll. [ 69 ].…”
Section: Design and Synthesis Of Polyphosphodiestersmentioning
confidence: 99%
“…Additionally, note that the efficient continuous flow method of the end-to-end preparation of cyclic phosphate monomers with a semi-continuous modular flow platform was developed very recently by Monbaliu and coll. [ 69 ].…”
Section: Design and Synthesis Of Polyphosphodiestersmentioning
confidence: 99%
“…Finally, it should be mentioned that 1 H NMR spectra in NMR solvents containing TMS are sometimes quite unexpectedly referenced with respect to residual signals. For example, in [103], the spectrum of product 1 (Figure 2) in CDCl 3 was related to the CHCl 3 line at 7.26 ppm [49,51], although TMS was visible at δ H −0.08 ppm (Figure S5). The colors of this spectrum strongly suggest that it was analyzed with MestReNova [60].…”
Section: Reference Of Nmr Spectra Using Methods A-current Statementioning
confidence: 99%
“…The line at −0.01 ppm (instead of 0.07 ppm), which most likely comes from silicone grease [49,51], reinforces this notion. Due to some structural similarities between 1 and hexamethylphosphoramide (HMPA, 2), which induces a large high-frequency shift of the CHCl3 signal [4], it is clear that the δH values reported in [103] were underestimated by 0.08 ppm, Figure 2. A similar case appears in [104], in which "NMR spectra were recorded ….…”
Section: Reference Of Nmr Spectra Using Methods A-current Statementioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Monbaliu et al reported the continuous-flow synthesis of cyclic phosphotriesters 19 that are useful as monomers of polyphosphoesters. [29] As mentioned in the introduction section, polyphosphoesters have been used as bio-compatible and bio-degradable polymers. The ring size of the cyclic monomer is important.…”
Section: Nucleophilic Substitutions Of Pcl 3 and Pocl 3 With Alcohol ...mentioning
confidence: 99%